Systematic characterisation and seed oil analysis in candidate plus trees of biodiesel plant, Pongamia pinnata - Kesari, V.; Krishnamachari, A.; Rangan, L. (Wiley, 2008)
Candidate plus trees (CPTs) of Pongamia pinnata, a potential biodiesel plant occurring across 10 locations in North Guwahati, were identified based on morphological markers (vegetative and reproductive) using combined analysis over locations. Identified CPTs were then multiplied using seed propagation technique in a nursery bed. The performance of the candidate trees with respect to seed and pod traits, the two most important characters with regard to oil, were evaluated using CROPSTAT software for inferring potential genotypes that can be included in programmes aimed at genetic improvement of the species. Total oil content from the seeds of plus trees was also analysed using solvent extraction procedure at their boiling points. Hexane extraction yielded maximum oil content from seeds (33%) compared with petroleum ether (30%). When the seed to solvent ratio varied, no significant difference was noticed on the total oil yield for an individual tree, although the recovery of solvent and the time taken for oil extraction were significantly reduced at higher ratios of solvent used.